PROPAGANDA POLITIK ADE ARMANDO DALAM MEDIA SOSIAL - Suhartono . Suhartono; Eti Yusnita; Hatta Azzuhri (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to determine Ade Armando's political propaganda and determine the impact of Ade Armando's political communication. The theory used in this research is the theory of political propaganda according to Harold D. Laswell. The research method used in this thesis is library research. tertiary sources come from books and journals regarding Ade Armando's political propaganda. The results of Ade Arrmando's political propaganda research in Indonesian politics which are conveyed through his social media uploads, be it Facebook, Instagram, or Twitter accounts. Behind the upload, his social media posts are written in sentences or photos that contain insults, insults, subtle satire to crude satire and there is a motive behind it, namely a sense of pride so that you feel great in every post that is always in the public spotlight, becomes a provocateur. There was an impact from Ade Armando's political propaganda, namely repeatedly being named a suspect with various legal violations up to Article 21 paragraph (1) and 21 paragraph (4) of the Criminal Procedure Code (KUHAP) because the person concerned had repeatedly made statements and statuses on social media that have the potential to divide the Republic of Indonesia. Apart from that, another impact that Ade Armando had was being the victim of a beating at the DPR/MPR building demonstration on Monday, April 11, 2022. Keywords: Political Communication, Ade Armando